Aberrant origin of left vertebral artery: a rare case - Kindra, Amanjeet S.; Gupta, Suneel K. (International Journal of Research in Medical Sciences, 2017)
The Vertebral Artery (VA) is classically described as originating as the first branch of the ipsilateral subclavian artery. The VA origin is variable and has been identified at the aortic arch, Common Carotid Artery (CCA), and Internal Carotid Artery. The VA arising from the carotid artery is an extremely uncommon variant. Left VA origin from the left CCA has been reported only thrice. These rare anomalous origins of the VA usually are asymptomatic. We describe symptomatic aberrant origin of left vertebral artery from left common carotid artery, a rare case.